Libel in the Blogosphere: Some Preliminary Thoughts - Glenn Harlan Reynolds (Washington University Law Review, 2006)
People have been talking about libel and bloggers since the blogosphere was new, but the big news at this point is that, so far at least, there’s more talk than action—despite the millions of blogs, and probable billions of blog entries to date, there haven’t really been any major blogrelated libel cases, and the number in total is quite small. People are still talking about Blumenthal v. Drudge, a case that predates the blogosphere, when they talk about blogs and libel, and no major new case has emerged to take its place. The absence of a major blog-related libel case in the United States after so much blogging is itself a pretty interesting phenomenon. In this short Essay, I will offer some suggestions as to why blog-related litigation has been relatively scarce, along with some observations on what law has developed, and some thoughts on the ways in which, and the extent to which, questions of blog-related libel should be treated differently than libel in newspapers, books, or television broadcasts.
Keywords: Internet; Libel & slander; Blogs; Freedom of speech; United States Constitution; United States